Blood meal organic fertiliser application on onion yield - Momtaz, N; Parvin, A; Hossain, MK; Saha, B; Moniruzzaman, M; Kibria, A; Sarker, MAM; Munshi, JL (Bangladesh Journal of Scientific and Industrial Research, 2021)
In this study, effects of bloodmeal on onion (Allium cepa L. CV. BARI peaj-1) cultivation to increase yield and related attributes have been tested. The effect of blood meal as fertilizers has been compared with growth hormone treatment and other conventional fertilizer. In the field, the different amount of growth elements treated were at the rate of 2550, 241.90 and 0.17 kg/ha for blood meal, urea and gibberellic acid (GA3), respectively. The yield performance was 172.84, 189.59 and 153.34 MT/ha for GA3, urea and blood meal, respectively. Using GA3 is expensive, and use of urea, a chemical fertilizer, can have adverse effect on soil. Blood meal, a biological ingredient, appears to be a bio-rationale amendment for production and sustained yield of onion. The results will need to ground truth tested in the field. Bangladesh J. Sci. Ind. Res.56(2), 87-94, 2021